THE IMPACT OF AI USAGE ON THE DEVELOPMENT OF PROBLEM-SOLVING SKILLS FOR DIGITAL TALENT HUMAN RESOURCES - Febri Pramudya Wardani; K.P.Suharyono Soemarwoto Hadiningrat; Dewanto Soedarno (JIPOWER : Journal of Intellectual Power, 2024)
The rapid adoption of Artificial Intelligence (AI) in various industries has significantly impacted the development of digital talent, particularly in enhancing problem-solving skills. This study aims to examine the impact of AI on the development of problem-solving abilities in digital talent. A quantitative research approach was used, with participants undergoing AI-assisted training designed to improve their problem-solving capabilities. Pre-test and post-test evaluations were conducted to measure changes in participants' problem-solving skills. The data were analyzed using statistical methods to identify significant differences before and after the AI intervention. The findings indicate that the use of AI positively contributes to the improvement of problem-solving skills among digital talent, providing insights into how AI can be leveraged to better prepare the workforce for the demands of the digital economy.